How and when does mental illness stigma impact treatment seeking? Longitudinal examination of relationships between anticipated and internalized stigma, symptom severity, and mental health service use. (October 2018) - Fox, Annie B.; Smith, Brian N.; Vogt, Dawne
Highlights: Examined longitudinal relationship between stigma and mental health treatment seeking. Internalized stigma mediated relationship between anticipated stigma and treatment. Symptom severity moderated relationship between anticipated stigma and treatment. Abstract: Although mental illness stigma has been identified as an important barrier to mental health treatment, there is little consensus regarding how and when mental illness stigma negatively impacts treatment seeking. The relationship between mental illness stigma and treatment seeking may depend on the particular stigma mechanism under investigation, as well as an individual's symptom severity. In the present study, we examined relationships between anticipated and internalized stigma, depressive symptom severity, and mental health service use using data from a two-wave longitudinal survey study of U.S. post-9/11 veterans. Mediated and moderated relationships were tested using PROCESS. Mediation analyses revealed that higher anticipated stigma led to higher levels of internalized stigma, which was associated with decreased treatment seeking. Moderation analyses revealed that anticipated stigma was only associated with treatment seeking when depressive symptoms were severe. The central role observed for internalized stigma highlights the value of stigma reduction efforts that focus on this stigma mechanism, whereas the finding that only those individuals with more severe symptoms are vulnerable to the negative effects of anticipated stigma underscores the importance of more targeted anti-stigma interventions.